STRATEGI PENGEMBANGAN USAHA PRODUKSI ROTI BALI KENCANA BAKERY, DENPASAR - Vrashinta Dewi, Ni Putu Kiki; Wrasiati, Ni Luh Putu; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 4 (2015): Desember, 2015)
This study aims to analyze the internal and external conditions and to develop and recommend business development strategies of Bali Kencana Bakery. Business Development Strategy Analysis using SWOT matrix, supported by quantitative analysis was using matrix EFE, IFE, IE, and QSPM. The result showed that the weighted value for the matrix Internal Factor Evaluation (IFE) was 3.11 (strong position) and External Factor Evaluation (EFE) was 2.64 (relatively moderate). In the matrix Internal External (IE) strategy that must be done was to grow and establish strategies (growth and build), which consists of an intensive strategy (market penetration , market development and product development) or integrative strategies (backward integration, forward integration and integration horizontal). There were nine alternative strategies can be drawn up to develop the business of Bali Kencana Bakery.
Keywords: 71